CORRECTION OF NASAL CONGESTION SYNDROME - Nuriddinov Khusniddin Noriddinovich (Web of Journals Publishing, 2025)
approximately 1/3 of the resistance ходитсяis applied to the movable part of the septum, the remaining 2/3 - to the area of the nasal valve. The resistance of the nose to air flow is due to various factors. First of all, the degree of nasal resistance depends on the vessels of the lower nasal concha. When blood stagnates in the cavernous venous plexuses, the shells swell and increase in size, which leads to narrowing of the nasal valve passage, sometimes to complete obstruction of the nasal cavity.